Performance enhancement and heat and mass transfer characteristics of direct evaporative building free cooling using corrugated cellulose papers. (15th November 2020) - Nada, S.A.; Elattar, H.F.; Mahmoud, M.A.; Fouda, A.
Abstract: In hot and dry climatic zones, direct evaporative cooling (DEC) system is used as an economical and efficient alternative to traditional air conditioning systems. The present paper concerns comprehensive experimental investigations and analysis of heat and mass transfer characteristics and thermal performance parameters of a bee-hive construction of corrugated-cellulose papers as a new cooling pad material. The performance parameters used to evaluate the effectiveness of the cooling pad materials are the outlet air temperature and relative humidity, pressure drop, humidifier effectiveness, rate of the evaporated water, sensible cooling capacity, specific cooling capacity (SCC), coefficient of performance (COP), specific water consumption (SWC), and Nusselt and Sherwood numbers. The cooling pad performance was investigated for a wide range of air and water temperatures and flow rates and pad thicknesses. The results show the enhancements of heat and mass transfer coefficients and the performance parameters with rising air temperature and water flow rate to humidifier. High values of the performance parameters ( h c  = 45 W/m 2 o C and h m  = 0.23 m/s, ε h u m  = 0.85 and COP = 170) are obtained compared to the traditional pad materials. Experimental correlations for the evaporative cooler performance parameters in terms of air and water temperatures and flow rates pad thicknesses are presented. Highlights: Cellulose paper, bee-hive structure has efficient thermal to be used as evaporator cooling pads. Good thermal-hydraulic characteristics at a wide range of operating and design conditions are obtained. Presented empirical correlations predict the performance parameters very well. High values of the performance parameters of the proposed cooling pad were obtained. The highest saturation efficiency is 84% with associated temperature and pressure drops 18 °C and 8 Pa.